JUAL BELI SISTEM KREDIT: TELAAH PENDEKATAN KAJIAN FIQH - Bahri, Anfal (IAI Darussalam, 2022)
This study explains credit when examined using the fiqh approach, because credit has become a polemic in society regarding the law. This study also discusses sharia, fiqh, and Islamic law, because many people have not been able to distinguish these terms. The method used in this study is a qualitative method of literature (library research). The results of this study indicate, a) fiqh as an approach is an activity and method of studying Islam through sharia law in the field of amaliyah based on detailed textual arguments. Sharia is a legal norm established by Allah that must be followed by Muslims based on faith in relation to Allah as well as to fellow human beings and things. Fiqh is sharia law relating to human actions taken from texts or other sources if they are not contained in the texts. Islamic law is a norm that comes from Allah and the Prophet Muhammad to regulate human behavior. b) If analyzed using the fiqh approach, basically buying and selling credit systems are allowed and there are no texts that forbid it. However, if it reaches the limit of injustice, then the law of credit turns into haram.